Ośrodki informacji jako instytucje wzmacniające ochronę ofiar wypadków drogowych na przykładzie działalności Ubezpieczeniowego Funduszu Gwarancyjnego i Motor Insurance Information Centre - Maśniak, Dorota (Information Centers as Institutions Strengthening Protection of Traffic Accident Victims on the Example of the Motor Insurance Information Centre and Insurance Guarantee Fund, 2008)
The 4th EU Motor Insurance Directive requires that details of every insured vehicle be accessible by a national information centre, in order to make cross-border claims less onerous. The information centre is responsible for collecting basic information concerning contracts of insurance against civil liability of motor vehicle holders as well as information about claims representatives appointed by insurance undertakings. The injured in accident can identify the insurer of the other party from the registration plate. In the UK, the Motor Insurers' Information Centre will fulfill this role. In Poland, the function of information centre is performed by the Insurance Guarantee Fund. The range of its tasks comprises administration of the register of the contracts of insurance against civil liability of holders of motor vehicles and gathering data concerning the participants of the event resulting with the liability of the insurance company under such contract as well as information on additional engineering examination which has been carried out after repair of the damaged vehicle. By broadening the information centre we need to consider the interest of entities because the protection of this interest is ratio legis for the information centre. The British solutions could be a good example of simple structural mechanisms which facilitate the victim's access to credible and up-to-date information.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1197, s. 243-251